" EXPLORING THE NEXUS OF LEADERSHIP STYLES AND EMPLOYEE MOTIVATION: A CASE STUDY OF THE PUBLIC SECTOR IN MAURITIUS " - Gunnoo, Leenshya; BINDAH, Eric; HASSEEA , Veeshall (The journal of contemporary issues in business and government, 2024)
Recognizing the critical importance of employee motivation in contemporary settings, government agencies and businesses alike are actively prioritizing strategies to boost staff morale. A central determinant of success in this endeavor is the leadership style adopted by managers, influencing their ability to inspire and effectively lead teams. This research is specifically focused on identifying the most effective leadership style within the public sector of Mauritius, with a primary objective of elevating employee motivation levels. Employing both descriptive and explanatory research strategies, the study utilizes a quantitative approach to provide numerical insights into the impact of leadership styles on employee motivation. The target population consists of public sector employees in Mauritius. Pearson Correlation and Multiple Linear Regression tests demonstrated significant positive correlations between leadership styles and employee motivation. Transformational leadership demonstrates a robust positive correlation, along with transactional leadership. Surprisingly, laissez-faire leadership also exhibits a positive correlation, suggesting autonomy may enhance motivation. Democratic leadership has a high positive correlation, and unexpectedly, autocratic leadership shows a positive correlation, challenging conventional perceptions.